Cascade Deep Forest With Heterogeneous Similarity Measures for Drug–Target Interaction Prediction - Zheng, Ying; Wu, Zheng (Frontiers in Genetics, 2021)
Drug repositioning is a method of systematically identifying potential molecular targets that known drugs may act on. Compared with traditional methods, drug repositioning has been extensively studied due to the development of multi-omics technology and system biology methods. Because of its biological network properties, it is possible to apply machine learning related algorithms for prediction. Based on various heterogeneous network model, this paper proposes a method named THNCDF for predicting drug-target interactions. Various heterogeneous networks are integrated to build a tripartite network, and similarity calculation methods are used to obtain similarity matrix. Then the cascade deep forest method is used to make prediction. Results indicate that THNCDF outperforms the previously reported methods based on the 10-folds cross-validation on the benchmark data sets proposed by Y.Yamanishi. The area under Precision Recall curve(AUPR) value on the Enzyme, GPCR, Ion Channel and Nuclear Receptor data sets is 0.988, 0.980, 0.938 and 0.906 separately. The experimental results well illustrate the feasibility of this method.